Strengthening Religious Moderation through an Integrated Curriculum Based on Islam Rahmatan Lil 'Alamin for Secondary School Teachers - Eliyyil Akbar; Muchamad Toif Chasani; Irfan Tamwifi; Ardian Al Hidaya (GUYUB: Journal of Community Engagement, 2025)
Religious moderation is a fundamental value that must be internalized in the education system to prevent the growth of extremism and intolerance. This study aims to strengthen the capacity of secondary school teachers in Central Aceh to integrate the values of religious moderation through a curriculum based on ISRA (Islam Rahmatan lil ‘Alamin). The method employed is a participatory community service approach, which includes the development of the ISRA curriculum module, workshops, intensive mentoring, and curriculum implementation assessments. The program involved teachers from various secondary schools in Central Aceh as the main participants.The results indicate a significant improvement in teachers’ understanding and ability to design and implement learning that reflects tolerant, inclusive, and peace-oriented Islamic values. The indicators of success include: (1) the development of an applicable ISRA curriculum module, (2) increased participant scores in pre-tests and post-tests, (3) enhanced pedagogical skills in embedding religious moderation into classroom practices, and (4) the formation of a teachers' community of practice promoting religious moderation in Central Aceh. Overall, this program successfully empowered teachers to transform the values of religious moderation into educational practices that foster diversity and social harmony.